Prevalence and predictors of prolonged length of stay among patients admitted under general internal medicine in a tertiary government hospital in Manila, Philippines: a retrospective cross-sectional study - John Jefferson V. Besa; Ella Mae I. Masamayor; Diana R. Tamondong-Lachica; Lia M. Palileo-Villanueva (BMC, 2023)
Abstract Background Prolonged hospitalization leads to poorer health outcomes and consumes limited hospital resources. This study identified factors associated with prolonged length of stay (PLOS) among internal medicine patients admitted in a tertiary government hospital. Methods We reviewed the medical records of 386 adult patients admitted under the primary service of General Internal Medicine at the Philippine General Hospital from January 1 to December 31, 2019. PLOS was defined as at least 14 days for emergency admissions or 3 days for elective admissions. Sociodemographics, clinical characteristics, admission- and hospital system-related factors, disease-specific factors, outcome on the last day of hospitalization, and hospitalization costs were obtained. We determined the proportion with PLOS and reviewed reasons for discharge delays. We conducted multiple logistic regression analyses to assess associations between various factors and PLOS. Results The prevalence of PLOS is 19.17% (95% CI 15.54, 23.42). Positive predictors include being partially dependent on admission (aOR 2.61, 95% CI 0.99, 6.86), more co-managing services (aOR 1.26, 95% CI 1.06, 1.50), and longer duration of intravenous antibiotics (aOR 1.36, 95% CI 1.22, 1.51). The only negative predictor is the need for intravenous antibiotics (aOR 0.14, 95% CI 0.04, 0.54). The most common reason for discharge delays was prolonged treatment. The median hospitalization cost of patients with PLOS was PHP 77,427.20 (IQR 102,596). Conclusions Almost a fifth of emergency admissions and a quarter of elective admissions had PLOS. Addressing factors related to predictors such as functional status on admission, number of co-managing services, and use of intravenous antibiotics can guide clinical and administrative decisions, including careful attention to vulnerable patients and judicious use of resources.